Advances in Mathematical Modeling of Gas-Phase Olefin Polymerization - Mohd Farid, Bin Atan; Mohd Azlan, Bin Hussain; Mohammad Reza, Abbasi; Mohammad Jakir, Hossain Khan; Muhamad Fazly, Bin Abdul Patah (MDPI AG, Basel, Switzerland, 2019)
Mathematical modeling of olefin polymerization processes has advanced significantly, driven by factors such as the need for higher-quality end products and more environmentally-friendly processes. The modeling studies have had a wide scope, from reactant and catalyst characterization and polymer synthesis to model validation with plant data. This article reviews mathematical models developed for olefin polymerization processes. Coordination and free-radical mechanisms occurring in different types of reactors, such as fluidized bed reactor (FBR), horizontal-stirred-bed reactor (HSBR), vertical-stirred-bed reactor (VSBR), and tubular reactor are reviewed. A guideline for the development of mathematical models of gas-phase olefin polymerization processes is presented.